Effect of age at first use of oral contraceptives on breast cancer risk: An updated meta-analysis. Issue 36 (September 2019) - Ji, Li-Wei; Jing, Chun-Xia; Zhuang, Su-Lian; Pan, Wei-Cheng; Hu, Xing-Po
Abstract: Background: We evaluated the relationship between the age at first use of oral contraceptives (OC) and breast cancer (BC) risk. Methods: We searched PubMed, Embase, and related reviews published through June 28, 2018, and used summary relative risk (RR) and 95% confidence intervals (CIs) to evaluate the cancer risks, and fixed-effects dose–response meta-analysis to assess potential linear and non-linear dose–response relationships. Results: We included 10 studies, with 8585 BC cases among 686, 305 participants. The pooled RR for BC was 1.24 (95% CI: 1.10–1.41), with moderate heterogeneities ( I 2 = 66.5%, P < .001). No significant publication bias was found ( P = .584 for Begg test, P = .597 for Egger test). A linear dose–response relationship between the age at first OC use and BC risk was detected ( P = .518 for non-linearity). Subgroup analyses were restricted to studies done by BC subtypes, region, sample size, follow-up time and study quality. Inconsistent consequences with no statistical significance were explored when limited to studies from Western countries, study quality <7, sample size <10, 000, follow-up time <5 years, and BC subtypes defined by estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor-2 (HER-2) expression status in tumor tissue. Sensitivity analyses indicated that our results were stable and reliable after removing each study in turn and omitting studies of adjusted unreported variables. Conclusion: A significant linear relationship between the age at first OC use and BC risk was confirmed. No further consistent differences are noted in multiple aspects of BC subtypes defined by progesterone or ER status. Abstract : Supplemental Digital Content is available in the text